Design of an Emulgel for Psoriasis Focused on Patient Preferences - Rita Sanches Oliveira; Diva Ferraz da Silva; Sandra Mota; Jorge Garrido; Ermelinda Manuela Garrido; José Manuel Sousa Lobo; Isabel Filipa Almeida (Applied Sciences, 2022)
Adherence to topical treatments is low and is known to be influenced by the vehicle properties. Betamethasone dipropionate (BD) is an anti-inflammatory steroid, used in psoriasis treatment in the form of an ointment, cream, or solution. The aim of this work was to develop a new vehicle for BD, focusing on the preferences of patients with psoriasis as a strategy to improve treatment adherence. Two vehicles with an aqueous external phase were explored: an emulgel and a hydrogel based on a cyclodextrin inclusion complex used to improve the aqueous solubility of BD. Since BD solubilization was not fully achieved in the hydrogel, only the emulgel was selected for further characterization. This new vehicle (emulgel) is characterized by its white, shiny appearance and good spreading properties. In comparison with petrolatum, a lower residue, higher evaporation rate, lower stickiness, and reduced ability to stain polyester fabric were observed. This vehicle also showed shear thinning behavior. The impact of this new vehicle on adherence to topical treatments should be further confirmed in clinical settings.